Surgical Profile of Patients Undergoing Submandibular Gland Excision in a Tertiary Care Centre - Parajuli, Ramesh; Limbu, Tilak Raj; Chalise, Kamana; Maharjan, Sushna (Journal of Institute of Medicine Nepal, 2025)
Introduction: Submandibular gland is a major salivary gland responsible for the production of saliva.Ithas to be surgicallyexcised for neoplastic and various non-neoplastic diseases.This study was aimed to evaluate the demographics, chief complaint, indications and complications of submandibular gland excision in a tertiary care hospital. Methods: It is a descriptive cross-sectional study of patients who underwent submandibular gland excision,from 1 January 2021 to 31 December 2023.Ethical approval was taken from the Institutional Review Committee of the hospital. Transcervical approach was used in all the patients.Patients were followed until discharge from the hospital. The intra-operative and immediate post operative complications were noted. Results: Out of 32 patients, 20(62.5%) were males and 12(37.5%) were females aged 8-62 years with 31-40 years being the most affected age group (31.2%). Painful submandibular swelling was complained by 18 (56.2%) patients as the most common complaint.The most common indication for surgery was the sialolithiasis in 13(40.6%) patients followed by sialadenitis in 8(25%) patients. Four (12.5%) patients were operated for the neoplastic diseases.Marginal mandibular nerve paresis was the commonest surgical complication that occurred in 3(9.3%) patients. One patient each (3.1%) had hematoma, residual stone and surgical site infection, respectively. Conclusion: Sialadenitis and sialolithiasis were the most common indications for the submandibular gland excision. Painful submandibular swelling was the most common presentation in the majority of the patients. Marginal mandibular nerve paresis was the commonest surgical complication.